2003
DOI: 10.1097/01.sla.0000081085.98792.3d
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Population and Its Impact on the Surgery Workforce

Abstract: The aging of the US population will result in significant growth in the demand for surgical services. Surgeons need to develop strategies to manage an increased workload without sacrificing quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
383
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 675 publications
(397 citation statements)
references
References 23 publications
2
383
0
12
Order By: Relevance
“…4 An increasing number of elderly patients will be undergoing surgery, leading to a projected 31% increase in general surgery workload. 5 In recent years, a standardized measure of a patient's physiologic reserve has been developed in an effort to predict postoperative morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…4 An increasing number of elderly patients will be undergoing surgery, leading to a projected 31% increase in general surgery workload. 5 In recent years, a standardized measure of a patient's physiologic reserve has been developed in an effort to predict postoperative morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Not surprisingly, cataract surgery by phacoemulsification and intraocular lens (IOL) implantation is the most commonly performed surgical procedure worldwide. 3,[5][6][7] Valid evaluation of cataract and its visual consequences is indispensable for the purpose of investigating possible risk factors for cataract formation and for documenting progression of cataract in epidemiologic and cohort studies. Also, reliable and valid assessment of cataract and its visual sequelae is equally important for clinical practice, if the ophthalmologist is to accurately evaluate the impact of age-related cataract on patient's visual performance and experience, and therefore identify those who are likely to benefit from surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, a further study conducted on the Hip and Knee specialist workforce identified a chasm between the 23 % increase in the demand for services but only a 2 % increase in supply of specialists. The issues that beseech predicting future supply and demand models stem from the unpredictable shift in demographics and the evolving spectrum of chronic disease [10]. On the supply side restructuring of training schemes and large scale reform of working patterns result in difficulties in forecasting the functional capacity of the orthopedic community.…”
Section: Concepts Of Workforce Planningmentioning
confidence: 99%